Expression of TAM-R in Human Immune Cells and Unique Regulatory Function of MerTK in IL-10 Production by Tolerogenic DC - Giroud, Paul; Renaudineau, Sarah; Gudefin, Laura; Calcei, Alexandre; Menguy, Thierry; Rozan, Caroline; Mizrahi, Jacques; Caux, Christophe; Duong, Vanessa; Valladeau-Guilemond, Jenny (Frontiers in Immunology, 2020)
Tumor infiltrating myeloid cells are a key component of the immune infiltrate often correlated with a poor prognosis due to their capacities to sustain an immunosuppressive environment. Among membrane receptors implicated in myeloid cell functions, Tyro3, Axl and MerTK which are a family of tyrosine kinase receptor (TAM-R) have been described in the regulation of innate cell functions. Here, we have identified MerTK among TAM-R as the major marker of both human M2 macrophages and tolerogenic DC. In situ, MerTK expression was found within the immune infiltrate in multiple solid tumors, highlighting its potential role in cancer immunity. TAM-R ligands Gas6 and PROS1 were found to be constitutively produced by myeloid cells in vitro. Importantly, we describe a novel function of MerTK/PROS1 axis in the regulation of IL-10 production by tolerogenic DC. Finally, the analysis of TAM-R expression within the lymphoid compartment following activation revealed that MerTK, but not Axl or Tyro3, is expressed on activated B lymphocytes and regulatory T cells, as well as CD4+ and CD8+ T cells. Thus, our findings deepen the implication of MerTK in the regulation of myeloid cells mediated immunosuppression and identified new cellular targets expressing MerTK that could participate in the antitumor immune response.